Efficacy of Hyperopic Photorefractive Keratectomy Simultaneously Performed With Phototherapeutic Keratectomy for Decreasing Hyperopic Shift. Issue 8 (August 2016) - Amano, Shiro; Kashiwabuchi, Kyoko; Sakisaka, Toshihiro; Inoue, Kenji; Toda, Ikuko; Tsubota, Kazuo
Abstract : Purpose: To investigate the efficacy of hyperopic photorefractive keratectomy (HPRK) that was performed simultaneously with phototherapeutic keratectomy (PTK) with regard to decreasing hyperopic shift. Methods: A total of 63 eyes of 47 consecutive patients with granular corneal dystrophy (GCD) or band-shaped keratopathy (BSK) underwent PTK or PTK + HPRK. PTK alone was performed in 40 eyes (20 GCD and 20 BSK), and PTK + HPRK was performed in 23 eyes (15 GCD and 8 BSK). All patients underwent examinations including uncorrected distance visual acuity, corrected distance visual acuity, refractometry, and keratometry before and at 1, 3, and 6 months after PTK. Medical charts were reviewed retrospectively. Results: Superficial corneal opacity was successfully removed from all eyes, and uneventful reepithelialization was completed within 7 days after PTK or PTK + HPRK. The average uncorrected distance visual acuity was significantly better in the PTK + HPRK group than in the PTK group preoperatively and at 1, 3, and 6 months postoperatively. The corrected distance visual acuities were similar in both groups preoperatively and postoperatively. The hyperopic change in the PTK group was approximately 1.5 diopters, and that in the PTK + HPRK group was almost zero. There were significant differences in the average changes of the spherical equivalent from preoperation between the PTK and PTK + HPRK groups at all postoperative time points. Conclusions: Simultaneous performance of PTK and HPRK can effectively reduce hyperopic shift after PTK and is as safe as PTK alone. It is recommended that HPRK be added to PTK to treat eyes in which hyperopic shift is undesirable.